Development of STEM-Oriented E-Module Integrated EDP Pattern SSI on Excretory System Material to Train Creative Thinking Skills of Junior High School - Sabillatush Oktaviani; Erti Hamimi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The rapid development of the times in the 21st century is characterized by technological advances with increasingly complex problems so that creative thinking skills are needed by students. E-modules with STEM approach in EDP pattern collaborated with SSI can train students' creative thinking skills. The purpose of this research is to produce a valid and practical e-module with STEM approach of EDP pattern integrated with SSI and to test its effectiveness in encouragingstudents' creative thinking skills on excretory system material. The development was carried out with the ADDIE model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. Qualitative data was obtainedthrough interviews with teachers, suggestions, and comments on the questionnaire. Quantitative data were obtained from the scores of validators, teachers, students, pretest and posttest. Data analysis used validity and reliability tests, normality tests,homogeneity tests, t-tests, and N-Gain tests. The results of the media and material validation test were 94.67% and 96.45%, respectively. The results of teacher and student practicality tests were 91.67% and 93.03%, respectively. The N-Gain test results showed a comparison of the effectiveness of low criteria in the control class and medium in the experimental class. It can be concluded that the developed e-module is valid, practical, and effective to train creative thinking skills.